Application of Kinesio Taping method for newborn swallowing difficultly: A case report and literature review. Issue 31 (August 2016) - Lin, Chien-Lin; Wu, Wei-Ting; Chang, Ke-Vin; Lin, Hong-Yi; Chou, Li-Wei
Abstract: Background: Preterm infants are at an increased risk of sucking problems, swallowing difficulty, and poor nourishment. During the neonatal period, the neurobehavioral organization of a preterm baby is poor compared with that of appropriate gestational age infants. Kinesio Taping has been widely used for edema control, joint protection, and proprioception training. With the help of augmentation of the sensory input for muscle facilitation and inhibition through tapping, the coordination of the target muscle groups can be improved. Until now, no research is available on the use of Kinesio Taping for the swallowing difficulty of infant. Methods: We reported a preterm infant suffering from brain edema at birth and swallowing difficultly until 40 weeks. The swallowing reflex was delayed. Moreover, lip closure and rooting reflex combined with the dysfunction grade of jaw movement were poor. We performed KT methods on the baby under the theory of the direction of the tape for facilitate or inhibit the muscle. Result: After the Kinesio Taping treatment, the sucking function was improved with good lip closure.One week later, the baby was discharged without the use of an oral gastric tube. Conclusion: Kinesio Taping contributed significantly to the improvement of impaired sucking and swallowing and could be implemented as a regular rehabilitative approach for infants suffering from these difficulties.